New insights into the regulation of stomatal movements obtained by metabolomics and physiological analyses - Lima, Valéria Freitas (2019)
Stomata are leaf epidermal structures consisting of two guard cells (GC) that surround a pore, in which the opening is actively regulated by changes in the accumulation of different osmolytes in GCs. The opening and closure of this pore regulate the atmospheric CO2 influx for photosynthesis as well as the water loss via transpiration. During stomatal opening, there is an increase in the volume of GCs caused by the intracellular entry and/or generation of solutes, such as potassium (K+) and malate (malate2-), which reduce the osmotic potential of these cells, creating a gradient favorable for the water influx and consequently, stomatal opening. The initial theory regarding GC osmoregulation suggested that the accumulation of sucrose had an osmoregulatory role in the symplast of GCs. However, recent results suggest that sucrose is degraded within guard cells during light-induced stomatal opening. In addition, it is also known that different metabolites from mesophyll cells, especially sucrose and malate, can induce changes in the stomatal opening. However, the mechanisms by which these metabolites influence stomatal movement remains unclear. Hence there is no consensus regarding the importance of these organic solutes in the regulation of stomatal movement, especially in primitive vascular plant groups such as ferns. Thus, this study aimed to investigate the role of the sucrose and malate in the stomatal opening and closure. In this context, the first chapter involves an update covering the multiple roles of sucrose in guard cell regulation, highlighting recent findings from metabolomic and systems biology studies. The second chapter involves an investigation of the role of leaf metabolites, specially, sucrose/malate ratio in responses to changes in light and atmospheric CO2 concentration in ferns and angiosperms.